Targeting CDK6 and BCL2 Exploits the "MYB Addiction" of Ph + Acute Lymphoblastic Leukemia - De Dominici, Marco; Porazzi, Patrizia; Soliera, Angela Rachele; Mariani, Samanta A; Addya, Sankar; Fortina, Paolo; Peterson, Luke F; Spinelli, Orietta; Rambaldi, Alessandro; Martinelli, Giovanni; Ferrari, Anna; Iacobucci, Ilaria; et al. (Cancer research (Chicago, Ill.), 2018)
Philadelphia chromosome-positive acute lymphoblastic leukemia (Ph ALL) is currently treated with BCR-ABL1 tyrosine kinase inhibitors (TKI) in combination with chemotherapy. However, most patients develop resistance to TKI through BCR-ABL1-dependent and -independent mechanisms. Newly developed TKI can target Ph ALL cells with BCR-ABL1-dependent resistance; however, overcoming BCR-ABL1-independent mechanisms of resistance remains challenging because transcription factors, which are difficult to inhibit, are often involved. We show here that (i) the growth of Ph ALL cell lines and primary cells is highly dependent on MYB-mediated transcriptional upregulation of CDK6, cyclin D3, and BCL2, and (ii) restoring their expression in MYB-silenced Ph ALL cells rescues their impaired proliferation and survival. Levels of MYB and CDK6 were highly correlated in adult Ph ALL ( = 0.00008). Moreover, Ph ALL cells exhibited a specific requirement for CDK6 but not CDK4 expression, most likely because, in these cells, CDK6 was predominantly localized in the nucleus, whereas CDK4 was almost exclusively cytoplasmic. Consistent with their essential role in Ph ALL, pharmacologic inhibition of CDK6 and BCL2 markedly suppressed proliferation, colony formation, and survival of Ph ALL cells and in mice. In summary, these findings provide a proof-of-principle, rational strategy to target the MYB "addiction" of Ph ALL. MYB blockade can suppress Philadelphia chromosome-positive leukemia in mice, suggesting that this therapeutic strategy may be useful in patients who develop resistance to imatinib and other TKIs used to treat this disease. .